2017
DOI: 10.1186/s13034-017-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

Youth in the midst of escalated political violence: sense of coherence and hope among Jewish and Bedouin Arab adolescents

Abstract: BackgroundDuring stressful events, individuals (particularly adolescents) from minority groups are often more vulnerable to distress. This claim will be examined in terms of coping resources and stress reactions to escalated political violence. This study aimed to compare coping resources and stress reactions among adolescents from two ethnic groups in southern Israel—Jews and Bedouin Arabs—during a period of escalated political violence (November 2012). The Bedouin Arab group is the ethnic minority of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In this study, we used the Arabic version of the SOC questionnaire. This version has been used in several previous research projects and has been found to be reliable and suitable for use among the Bedouin Arab population [23,70,71]. In the current study, the internal consistency reliability for the scale was 0.80.…”
Section: Sense Of Coherence (Soc) Questionnairementioning
confidence: 61%
See 2 more Smart Citations
“…In this study, we used the Arabic version of the SOC questionnaire. This version has been used in several previous research projects and has been found to be reliable and suitable for use among the Bedouin Arab population [23,70,71]. In the current study, the internal consistency reliability for the scale was 0.80.…”
Section: Sense Of Coherence (Soc) Questionnairementioning
confidence: 61%
“…Previous research on SOC in Eastern-collectivistic contexts such as the Arab minority in Israel has revealed two important findings. First, researchers found lower levels of SOC among the Arab minority [23,31]. Second, over time, changes in SOC levels were observed (higher levels) and SOC became a strong predictor of stress reactions [24].…”
Section: Sense Of Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted among a general population in the eastern Democratic Republic of Congo concluded that cumulative exposure to political violence is inversely correlated with SOC (Pham, Vinck, Kinkodi, & Weinstein, 2010). It was proposed that living in areas of political violence with unstable and disorganized living conditions, low socio-economic standards, weak generalized resistance resources, and a different perception of the SOC construct, could give lower SOC scores (Abu-Kaf, Braun-Lewensohn, & Kalagy, 2017;Braun-Lewensohn & Sagy, 2011a, 2011bBraun-Lewensohn & Sagy, 2010). Furthermore, previous studies have found that SOC scores diminished in patients with chronic diseases and attributed this to negative life events and/or health deterioration (Bergman et al, 2011;Gauffin et al, 2010;Merakou et al, 2013).…”
Section: Findings From the Viewpoint Of The Ecological Modelmentioning
confidence: 99%
“…22 include examples from the salutogenesis literature, the sense of coherence approach offers insights into the mobilizing orientation behind political violence as well as the psychological capacity to resist and overcome these oppressive and destructive forces. 23 Antonovksy's early work on the origins of health after genocide took place at a historical moment when the intensification of settler colonial processes in Israel were ramping up systemic displacement, exclusion, and violence against Palestinians in the occupied territories. 24 For Antonovsky, the health of the Israeli state seems necessarily embodied in the shared coherence of individual Israeli settlers.…”
Section: Orienting the Micro-foundations Of Genocide Preventionmentioning
confidence: 99%